Pemanfaatan Limbah Kertas Koran Sebagai Nail Art Extension - Sofia Daniati; Kartika Dewi Graseliyanti; Widiati Alifah (Garina, 2023)
The amount of newspaper waste makes the writer want to use newsprint as the basic material for making nail art extensions as a new innovation in the nail art field. This research was conducted with the methods of observation, documentation, literature, experiments, interviews and questionnaires. The manufacture of nail art extensions using newspaper waste is carried out in 3 stages, namely, the preparation of tools and materials, the process of making nail art extensions using newspaper waste and the final stage of using nail art extensions on fingernails. The feasibility of nail art extensions using newsprint waste, the color indicator has an average value of 4 which is declared feasible, the shape indicator has an average value of 4.5 which is considered quite feasible, the texture indicator has an average value of 4 which is considered quite feasible, the ease of application indicator obtains an average value. an average of 4.5 was declared quite feasible and the product design indicators obtained an average value of 4.3 with a fairly decent category. The results of a public test conducted on 38 respondents can be concluded that 94% like nail art extension products from newsprint waste. The results of this study produce a product that has a unique and attractive design because of the pattern of waste newsprint that makes the product look aesthetic. Thus, it can be concluded that nail art extension products using newsprint waste are quite feasible to use.